1990
DOI: 10.1111/j.1365-2141.1990.tb07877.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of 147 cases of non‐Hodgkin's lymphoma: non‐random chromosomal abnormalities and histological correlations

Abstract: A prospective cytogenetic study of patients with non-Hodgkin's lymphoma (NHL) presenting to one institution was commenced in 1983 as part of a larger study including histology, immunophenotyping, cytokinetics and survival. 175 patients were studied over 5 years and G-banded karyotypes were successfully obtained in 147. Chromosome abnormalities were detected in 135 cases (92%) with the commonest abnormality being t(14;18)(q32;q21) in 69 cases. Other non-random translocations were much less frequent, i.e. t(11;1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…[26][27][28][29][30][31] In some studies, changes such as trisomies of chromosomes 2/2p, 3/3p, 5, 6, or 18, monosomy 7, del(6q), abnormalities of 17 [Ϫ17, del(17p), i(17q)], and breaks or duplications of 1q have been shown to correlate with advanced stage disease and poor prognosis. 13,19,[32][33][34][35][36] In the present study, SKY analysis identified 3 sites (2q31, 3q27, 7q22) that significantly associated with advanced-stage disease or poor treatment response. Two of these, 2q31 and 7q22, have previously not been described by G-banding studies.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…[26][27][28][29][30][31] In some studies, changes such as trisomies of chromosomes 2/2p, 3/3p, 5, 6, or 18, monosomy 7, del(6q), abnormalities of 17 [Ϫ17, del(17p), i(17q)], and breaks or duplications of 1q have been shown to correlate with advanced stage disease and poor prognosis. 13,19,[32][33][34][35][36] In the present study, SKY analysis identified 3 sites (2q31, 3q27, 7q22) that significantly associated with advanced-stage disease or poor treatment response. Two of these, 2q31 and 7q22, have previously not been described by G-banding studies.…”
Section: Discussionmentioning
confidence: 92%
“…The types of chromosomal rearrangements are diverse and include translocations, deletions, duplications, and several undefined aberrations such as additions and marker chromosomes. 4,12,[18][19][20][21] This study is the first reported to use SKY to fully characterize the chromosomal rearrangements in a panel of histologically reconfirmed DLBCL. In more than 90% of the cases, SKY provided additional cytogenetic information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that LB1 expression might be related to morphologic characteristics of lymphomatous cells, which could re¯ect the B lymphocyte dierentiation stage aected by the neoplastic process, or other illde®ned cellular processes associated with these particular morphologic aspects. Interestingly, the LB1 gene was mapped to chromosome 13 at band q14, a region that is rearranged by translocations or interstitial deletions in about 10% DLBL (Juneja et al, 1990;Whang-Peng et al, 1995 and Chritian Bastard, personal communication). As LB1 is highly expressed in some lymphoid tissues and deregulated in DLBL, it is tempting to speculate that it might be involved in the reorganization of the cytoskeleton associated with lymphocyte polarization, mobility, or signalling pathways initiated by the activation of adhesion, cytokine or antigen receptors (Gomez et al, 1997;Juglo and Jongstra-Bilen, 1997;Lub et al, 1997;Manie et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From abnormalities have been described in FL. [66][67][68][69][70][71][72] Additional chromosomal abnormalities involving, for example, p53, play a central role in the progression of FL. These additional abnormalities are likely to be important in the development of the disease, because Bcl-2/IgH is necessary but not sufficient for tumor development.…”
Section: Org Frommentioning
confidence: 99%